Investigation of the effects of combined exercises and self-management education, with and without functional exercises, on pain and functional outcomes in patients with avascular necrosis of the femoral head: a protocol for a single-blind, randomised controlled trial with a parallel design and a 4 month follow-up - Zohreh Gholami; Seyedeh Tahereh Faezi; Elham Madreseh; Raghad Mimar (BMJ Open Sport & Exercise Medicine)
Non-traumatic avascular necrosis of the femoral head (AVNFH) is a progressive condition that often affects young individuals, leading to bone death and eventual collapse. This degeneration is causing pain and limited function in daily activities over time. This study will plan to enrol 53 male and female participants, aged 18–50 years, who have been diagnosed with AVNFH. Participants will be randomly assigned to one of two groups: (1) the Exe+Functional group, which will receive 12 weeks of mixed therapeutic exercises combined with functional resistance exercises and self-management education and (2) the control group, which will receive the same interventions but without functional exercises. The Exe+Functional group will engage in two times per week sessions of low-intensity resistance, and mobility exercises, along with a one time per week functional exercise session. The control group will have 3 weekly sessions of low-intensity exercises (resistance and mobility) without functional exercises. The primary outcomes of the study will be pain, measured using a Visual Analogue Scale (VAS) and functional pain, assessed using a Numeric Rating Scale (NRS). Secondary outcomes will include the Harris Hip Score, the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) for hip osteoarthritis, the Timed Up and Go (TUG) test, the 30 s Chair Stand Test, active range of motion, muscle strength and the 10-metre walk test. Data will be collected at baseline (preintervention), postintervention at 12 weeks and at a 4 month follow-up. Trial registration number: IRCT20220510054814N2.